METHODOLOGICAL SUPPORT FOR BASKETBALL TEACHERS OF HIGH SCHOOL STUDENTS IN PHYSICAL EDUCATION CLASSES - YULDASHEV , Noibjon («PHYSICAL CULTURE: UPBRINGING, EDUCATION, TRAINING», 2025)
This article examines the methodological support provided to teachers teaching basketball to 11th-grade students during physical education classes. The importance of physical education for developing health, moral, and willpower qualities, as well as for improving the educational level of high school students, is emphasized. Experimental studies were conducted to develop and implement a system of methodologi- cal support for physical education teachers, including individual and group approaches, preparation of teaching materials, and monitoring student knowledge and skills acquisition.